Protecting your web applications : solutions and strategies to combat cybersecurity threats - Sloper, Gary; Hess, Ken (O'Reilly Media, 2019)
Websites, applications, and online services are critical business assets, but these services are also among the most vulnerable to attack. When cyberthreats succeed, your company can quickly drop customers, lose revenue, and suffer brand damage. This practical ebook explores today's major threat patterns and provides security professionals with strategies and techniques for preventing and protecting against a host of attacks. Gary Sloper, a vice president at Oracle Dyn, and industry journalist Ken Hess examine current dangers to cloud-based everything-as-a-service (XaaS) offerings--a threat landscape as big and diverse as the internet itself. You'll learn how attackers have become successful and explore current remedies to counteract their efforts. This ebook also looks at the future of web application protection according to industry experts. Get an overview of today's top cyberthreats and their impact on businesses Protect web applications from evolving threats using an integrated approach Use industry guidelines to help prevent injection, XSS, and session hijacking attacks Learn why companies are moving threat protection to third-party entities and the cloud Build layered security with firewalls, multifactor authentication, AI, secure programming, and data analytics.